The Maqashidiyya Dimension of Ibn Taymiyyah's Thoughts on Jihad - Pratama, Yoga (UIN Mataram, 2023)
This research aims to examine the Maqashidiyah dimensions (sharia goals) in Ibn Taimiyah's thoughts about jihad. Ibn Taimiyah's thoughts on jihad are analyzed in the context of Maqashid al-Shariah which includes the maintenance of the soul, the maintenance of the mind, the maintenance of religion, and the maintenance of property. The research method used is literature study by analyzing relevant works of Ibn Taimiyah, especially in relation to jihad. Research findings show that in his thinking, Ibn Taymiyah viewed jihad as a legitimate form of self-defense to protect the lives and safety of Muslims from oppression, aggression and threats of violence. Jihad also involves protecting the thoughts and beliefs of Muslims from influences that corrupt the mind, as well as the spread of Islamic teachings as part of intellectual jihad. Apart from that, Ibn Taimiyah saw jihad as an effort to defend the Islamic religion from the threat of disbelief,maintaining the continuity of religion, and fighting injustice. Protection of Muslim property was also a concern of Ibn Taymiyah in the context of jihad, with an emphasis on protecting Muslim wealth and defending their rights. This research provides a deeper understanding of the Maqashidiyah dimension in Ibn Taimiyah's thinking about jihad and contributes to the development of thinking about jihad in a broader context.